2012
DOI: 10.4028/www.scientific.net/amr.455-456.1251
|View full text |Cite
|
Sign up to set email alerts
|

Exergetic Assessment of Biogas Engine-Driven Heat Pump Systems for Using Sewage Resource

Abstract: In order to improve energy utilization rate of biogas engine-driven heat pump (BEHP) systems for wastewater treatment plant, the exergy analysis is applied in this paper. The paper concludes the exergy losses and exergy efficiency of each equipment, and reveals the weak link of energy transformation of the whole system. According to the calculation of one example, the location of maximum exergy loss is the biogas engine-driven, while the location of minimum exergy efficiency is the compressor, which provides p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Li et al [16] reported an exergy analysis of a biogas GEHP developed by starting with a mathematical model.…”
Section: Harbin Institute Of Technology China (2012)mentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al [16] reported an exergy analysis of a biogas GEHP developed by starting with a mathematical model.…”
Section: Harbin Institute Of Technology China (2012)mentioning
confidence: 99%
“…In [16], a biogas engine-driven heat pump has been evaluated on an exergy basis, developing a mathematical model.…”
mentioning
confidence: 99%